Perimetri : Incontri Internazionali d'Arte. - Bonito Oliva, Achille; Palazzo Taverna, Roma; Incontri Internazionali d'Arte, 1978, Roma (Roma : Incontri Internazionali d'Arte, 1978)
Benveduti, Maurizio ; Buren, Daniel ; Catalano, Tullio ; Christo ; Fabro, Luciano ; Jonas, Joan ; Kosuth, Joseph ; Kounellis, Jannis ; Mattiacci, Eliseo ; Mauri, Fabio ; Morris, Robert ; Patella, Luca ; Pisani, Vettor ; Pistoletto, Michelangelo ; Smith, Jack ; Toroni, Niele
Perimetri : Incontri Internazionali d'Arte, Palazzo Taverna, Roma, Maggio - Giugno 1978
boek